Analisis Tingkat Kesehatan Bank dengan Metode RGEC - Siti Rohimah; Arya Samudra Mahardhika (Jurnal Ilmiah Akuntansi Kesatuan, 2022)
This study aimed to determine the level of bank soundness with the RGEC method at PT. Bank Negara Indonesia (Persero), Tbk., and PT. Bank Syariah Indonesia, Tbk. The type of research used in this research is descriptive quantitative research. The type of data used is secondary data sourced from the analysis of the financial statements of PT. PT. Bank Negara Indonesia (Persero), Tbk., and PT. Bank Syariah Indonesia, Tbk. Based on the results of research on the health level of PT. Bank Negara Indonesia (Persero), Tbk., during the 2019-2020 period BNI bank was said to be healthy, and PT. Bank Rakyat Indonesia Syariah, Tbk shows that during the 2019 period, BSI banks were said to be less healthy because the NPL and LDR ratios were below the standard, namely 7% and 20%, respectively. In the period of 2020 PT. Bank Syariah Indonesia, Tbk has increased, namely the BRIS bank is said to be healthy.